The Effectiveness of Augmented Reality-Based Learning Media in Improving Vocabulary Mastery of Early Childhood in Makassar City - Amal, Azizah; Rusmayadi; Tri Sugiarti (Universitas Pendidikan Ganesha, 2025)
Vocabulary acquisition in early childhood is a fundamental aspect of language and communication development. However, current conditions indicate that children's vocabulary growth remains suboptimal, particularly in verb usage, adjectives, and descriptive words. This study aims to analyze the effectiveness of Augmented Reality (AR)-based learning media in enhancing vocabulary mastery among early childhood learners. The research employed a pre-experimental method with a one-group pretest-posttest design. The participants consisted of 15 early childhood learners selected through purposive sampling based on low vocabulary mastery criteria. Data were collected using vocabulary mastery tests, observation, and documentation. The data analysis techniques included descriptive statistics and the Wilcoxon non-parametric test. The findings indicate that the use of AR-based learning media significantly improves children's vocabulary mastery. The children demonstrated higher engagement during the learning process, which positively influenced their understanding of the vocabulary presented. AR media provided an enjoyable and interactive learning experience, increasing children's motivation and interest in learning. The study concludes that AR-based learning media is effective in improving vocabulary mastery in early childhood and holds important implications for the development of innovative, technology-based instructional tools to support early language learning.